2003
DOI: 10.1891/jnum.11.1.29.52062
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cultural Competence Assessment Instrument

Abstract: This article describes initial testing of an instrument designed to provide evidence of cultural competence among health care providers and staff. The Cultural Competence Assessment (CCA) instrument was based on a model describing cultural competence components (fact, knowledge, attitude, and behavior). Content and face validity were confirmed through expert panel review, subject feedback, and field-testing. The CCA was administered to an interdisciplinary health care team in a community hospice setting. Preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 7 publications
2
134
0
2
Order By: Relevance
“…This difference in number of items retained in each component may be related to the depth of the theoretical explanations of these components. Our final scale with 43 items is longer than many of the other published cultural competence scales which contain 20 to 31 items (e.g., see [12,15,[42][43][44]). This difference could be related to the richness of theoretical meanings underpinning the CCC model.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in number of items retained in each component may be related to the depth of the theoretical explanations of these components. Our final scale with 43 items is longer than many of the other published cultural competence scales which contain 20 to 31 items (e.g., see [12,15,[42][43][44]). This difference could be related to the richness of theoretical meanings underpinning the CCC model.…”
Section: Discussionmentioning
confidence: 99%
“…In a study among acute care nurses, Cronbach alpha for the CCA was 0.89; 0.76 for the CAS subscale; and 0.93 for the CCB subscale . Content and face validity of the CCA were initially established by a panel of expert reviewers and also supported in contrasted groups validity tests (Schim et al, 2003). An examination of concurrent validity between Campinha-Bacote's (1999) Inventory for Assessing the Process of Cultural Competence among Healthcare Professionals (IAPCC) and the CCA revealed that scores from the CCA moderately correlated (r = 0.66) with those from the IAPCC (Schim et al, 2003).…”
Section: Instrumentsmentioning
confidence: 99%
“…Over the past 5 years, the CCA has been used in numerous studies identifying the cultural competence of various health care professions. 12,13 The self-administered inventory consists of 30 questions on a 7-point Likert scale (1 5 strongly agree to 7 5 strongly disagree) that assesses 4 constructs of culturally competent care: cultural diversity, cultural awareness, cultural sensitivity, and cultural competence. 13 Each construct is operationally defined.…”
Section: Surveymentioning
confidence: 99%
“…12,13 The self-administered inventory consists of 30 questions on a 7-point Likert scale (1 5 strongly agree to 7 5 strongly disagree) that assesses 4 constructs of culturally competent care: cultural diversity, cultural awareness, cultural sensitivity, and cultural competence. 13 Each construct is operationally defined. Cultural diversity is the difference between groups based on distinguishing factors, such as race, ethnicity, national origin, sexual orientation, sex, ideology, language, disability, and generation.…”
Section: Surveymentioning
confidence: 99%